Assessing the impact of China's agricultural subsidy reform on fertilizer management: a county-level empirical analysis based on difference-in-difference model - Fan, Dongshou; Yang, Fuxia (Frontiers in Sustainable Food Systems, 2024)
Agricultural subsidies are widely acknowledged to be a crucial cause in food security and environmental protection, with a substantial impact on fertilizer consumption. China is also attempting to promote the green transformation of agricultural subsidies and sustainable food production. Existing research has explored the impact of China's agricultural subsidies reform (ASR) on farmers' fertilizer application behavior at household level, but little is known about the overall effect of ASR at the regional level. This paper investigates the effect of on fertilizer inputs using the staggered difference-in-difference (DID) approach, based on county-level panel data for 723 counties in China's Main Grain Producing Area (MPA) from 2013 to 2020. The results show that the ASR obviously increases fertilizer consumption by 5-6% in MPA during the study period. An analysis of mechanism reveal that ASR boosts fertilizer input through increased grain output and on-farm employment, which both play a 13.83% and 6.42% partial mediator role. Conversely, the growth of planting scale is the primary conduit for fertilizer reduction, accounting for 11.78% of the total. Furthermore, this positive effect is significantly lower in counties with low farmer disposable income or high agricultural mechanization than in others. These findings offer valuable insights for other developing countries aiming to promote green transformation of agriculture.